Deep Venous Thrombosis (DVT) in Lower Extremity Amputation as Cause of Pulmonary Embolism - Montserrat Pérez Pinar; Regina Pastor Toledo; Antonio Hernandez Castro; Julián Solís García del Pozo (European Journal of Case Reports in Internal Medicine, 2015)
The authors describe the case of a 43-year-old man with a right-leg knee amputation performed 14 years prior. He presented to hospital with dyspnea. A pulmonary embolism was detected. A Doppler ultrasound test showed deep vein thrombosis (DVT), which affected the stump of the amputated limb. When a pulmonary embolism is detected in a patient with an amputated lower limb, an exploration of the stump should be performed to rule out this uncommon complication.